Exploring the psychological factors of consumer purchase behavior in Bangladesh on the adoption of digital payment apps - Karmaker, Samanta; Oishi, Mst. Elma Fardouse; Qasem, Abrar; Sami, Shad Been Sharif (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.